Internet-Based Hospital Health Monitoring System for Patient - Mohammad Khair, Muhammad Zahirul Iqbal (Journal of Computing Technologies and Creative Content, 2019)
The improvements of medical technologies, medicine and techniques in developing countries has resulted an extraordinary increase in the life expectancy of these countries. This project takes a look at the development of a straightforward device that will be equipped for exchanging the information or data of a patient's body internal changes which is the heart beat rate to a wireless device. The need of this project is to reduce the trouble that is experienced by the doctors and staff of the hospital in observing different patients simultaneously. This project will empower them to observe patients without being physically present at the patient's ward, be it in the hospital or in their home. A patient's heart beat rate are wirelessly tranferred through an operator, which is the Wifi module.